PELAKSANAAN PENDIDIKAN DAN PELATIHAN APARATUR DALAM MENINGKATKAN KINERJA PEGAWAI DI KANTOR DINAS PERTAMBANGAN DAN ENERGI KABUPATEN KUTAI BARAT TAHUN 2015 - Fransiska Xeviria; Achmad Djumlani; Bambang Irawan (Magister Administrasi Publik FISIP Universitas Mulawarman, 2017)
The purpose of this study is to describe and analyze the implementation of education and training will be undertaken by the office of the Department of Mines and Energy of Kutai Barat in improving the performance of employees. As well as what are the constraints faced by the office of the Department of Mines and Energy of Kutai Barat in improving the performance of employees. The study concluded that the implementation of education and training for the State Civil Apparatus in the West Kutai Distamben left entirely to BKD appoint competent agency organizes. While this type of education and training undertaken by Education and Training Structural and Functional Education and Technical Training. While the material is given in the process of education and training adjusted based on the level that followed.